2012
DOI: 10.1002/ar.22631
|View full text |Cite
|
Sign up to set email alerts
|

Steep Increase in Myonuclear Domain Size During Infancy

Abstract: We investigated whether myonuclear number increases in proportion to the increase in fiber size during maturational growth of skeletal muscle. Thoraco-abdominal muscle tissue was obtained from twenty 6-day to 15-year-old boys and girls during cardiothoracic surgery. Cross-sections were stained by anti-laminin for the basal lamina and by DAPI to identify nuclei. Basal lamina was traced on digital images to measure the fiber cross-sectional area (FCSA). Nuclei located within the basal lamina were considered myon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…After incubation with the appropriate fluorescent-labeled secondary antibodies (Goat anti-rabbit IgG AlexaFluor 555 for CD31, Goat anti-mouse IgG1 AlexaFluor488 for Pax7, Goat anti-rabbit IgG AlexaFluor350 for laminin and Goat Anti-mouse IgM AlexaFlur488 for A4.840, all from InVitrogen/Moleculr Probes) and DAPI-stain (30 nM, Invitrogen) for nuclei, sections were mounted in Mowiol. Images were captured with a Nikon E800 fluorescence microscope 44 .…”
Section: Methodsmentioning
confidence: 99%
“…After incubation with the appropriate fluorescent-labeled secondary antibodies (Goat anti-rabbit IgG AlexaFluor 555 for CD31, Goat anti-mouse IgG1 AlexaFluor488 for Pax7, Goat anti-rabbit IgG AlexaFluor350 for laminin and Goat Anti-mouse IgM AlexaFlur488 for A4.840, all from InVitrogen/Moleculr Probes) and DAPI-stain (30 nM, Invitrogen) for nuclei, sections were mounted in Mowiol. Images were captured with a Nikon E800 fluorescence microscope 44 .…”
Section: Methodsmentioning
confidence: 99%
“…In animal studies, the Pax7 antigen is the most widely used marker to identify satellite cells (Olguin and Olwin, 2004 ; Kuang et al, 2006 ; Relaix et al, 2006 ; Zammit et al, 2006 ; Day et al, 2007 ; Ishido et al, 2009 ; Lepper et al, 2011 ; McCarthy et al, 2011 ; Murphy et al, 2011 ; Sambasivan et al, 2011 ; Jackson et al, 2012 ) and has been proposed to be the most reliable marker for satellite cells in mouse muscle (Kuang and Rudnicki, 2008 ; Zammit, 2008 ). In the past decade, an increasing number of human studies have utilized the Pax7 antibody for the identification of skeletal muscle satellite cells in vivo (McLoon and Wirtschafter, 2003 ; Reimann et al, 2004 ; Verdijk et al, 2007 ; McKay et al, 2008 ; Mackey et al, 2009 ; McKay et al, 2009 ; Kottlors and Kirschner, 2010 ; McKay et al, 2010 ; Mackey et al, 2011a ; Toth et al, 2011 ; McKay et al, 2012 ; Menon et al, 2012 ; Nielsen et al, 2012 ; Theriault et al, 2012 ; Walker et al, 2012 ; Bankole et al, 2013 ; Cermak et al, 2013 ; Delhaas et al, 2013 ; Joanisse et al, 2013 ; McKay et al, 2013 ; Suetta et al, 2013 ; Bellamy et al, 2014 ; Farup et al, 2014a , b ; Fry et al, 2014a ; Grubb et al, 2014 ; Kern et al, 2014 ; Mackey et al, 2014 ; Snijders et al, 2014b , c ; Theriault et al, 2014 ). Reimann et al ( 2004 ) compared M-Cad and Pax7 in biopsies taken from healthy and pathological human muscle.…”
Section: Satellite Cell Identification In Human Skeletal Musclementioning
confidence: 99%
“…During this stage there is extensive fusion of myoblasts into the elongating growing myofibers (hyperplasia), but after this time the increasing myofiber size is due mainly to hypertrophy (with minimal change in myonuclear number) ( Fig. However, an interesting recent paper (Delhaas, Van der Meer, Schaart, Degens, & Drost, 2013) investigated this aspect of myonuclear domain size in growing thoracoabdominal muscles of humans (aged 0.2 months to 15 years) and concluded that satellite cell density steeply declines in early infancy. The reason for this striking transition from hyperplasia to hypertrophy during growth is not known and has not been widely investigated for other species.…”
Section: Mechanisms Of Muscle Hypertrophymentioning
confidence: 99%
“…9.3B) (White et al, 2010). As a result, the myonuclear domain area [mm 2 ] increases rapidly in the first months after birth and reaches adult values in the young adolescent phase (Delhaas et al, 2013). However, an interesting recent paper (Delhaas, Van der Meer, Schaart, Degens, & Drost, 2013) investigated this aspect of myonuclear domain size in growing thoracoabdominal muscles of humans (aged 0.2 months to 15 years) and concluded that satellite cell density steeply declines in early infancy.…”
Section: Mechanisms Of Muscle Hypertrophymentioning
confidence: 99%